Effects of uv protectants and phagostimulants on the effectiveness of spray dry formulations of Spodoptera litura nucleopolyhedrovirus - Ithnin, Nazli Huda (2014)
Local Spodoptera litura nucleopolyhedrovirus (SpltNPV) was formulated using the spray-drying technique to examine its effectiveness in controlling Spodoptera litura. A total of seven UV protectants (Indian ink, coconut oil, albumen, charcoal, Tinopal LPW, molasses and lignin) were prepared for sunlight and UVB exposure tests. After 16 cumulative hours direct sunlight exposure, Spodoptera litura NPV treated with albumen, charcoal, Tinopal LPW, molasses and lignin caused more than 80% larval mortality after 96 hours post inoculation. UVB had caused a seven-fold reduction in Spodoptera litura NPV effectiveness; however, treatment with Tinopal LPW, molasses and lignin managed to protect the virus with the percentage larval mortality scored at 60%, 56%, and 66%, respectively, after 96 hours post inoculation. A total of 13 materials were tested for their phagostimulant characteristics, namely wheatgerm flour, molasses, cabbage, pegaga, sweet potato, caixin green, dwarf mustard, lettuce, Chinese kale, chilli leaf, chilli, Chinese mustard, and mustard extract. The materials were tested on the food preference of S. litura larvae based on the time taken for the larvae to have the first bite. Spodoptera litura NPV treated with plant aqueous extracts, such as cabbage (54.6 seconds), pegaga (56.2 seconds), sweet potato leaf (59.0 seconds), caixin green (80.4 seconds), dwarf mustard (91.2 seconds), and lettuce (92.2 seconds) recorded a shorter mean time for the larvae to have the first bite compared to the untreated virus (110.3 seconds). The aqueous extracts of these plants were further tested for their impact on the larval food consumption and larval mortality. Among them, the aqueous extracts of cabbage, pegaga and sweet potato leaf showed a promising phagostimulant effect on S. litura larvae. The second, third and fourth instar larvae of S. litura had highly consumed the cabbage, pegaga and sweet potato. The weight gain of the second, third and fourth instars of S. litura larvae showed a positive correlation to the food consumption. Higher larval weight gain was recorded in the older instar with higher food intake resulted in higher larval mortality. The three aqueous extracts recorded significant larval mortality in the second and third instar S. litura larvae after 72 hours post inoculation. The effect of these extracts on the fourth instar larval mortality was reduced. Based on the screening tests, Tinopal LPW, molasses, lignin, cabbage extract, pegaga extract and sweet potato extract were chosen for Spodoptera litura NPV formulation. A combination of three UV protectants, three phagostimulants and two multipurpose materials were used to form 18 spray-dried Spodoptera litura NPV formulations. Based on the electron microscopic examinations, the calculated size of the microgranules ranged between 3 to 10 μm. The formulations labelled as F1, F2, and F3 recorded higher percentage larval mortality after 72 hours post inoculation. Based on this study, Tinopal LPW is a promising UV protectant for Spodoptera litura NPV, and the plant extracts of cabbage, sweet potato and pegaga could enhance the palatability of the formulation.